Learning, Teaching, and Demonstration of Unique Chemistry for the Indonesian Generation at Sanggar Bimbingan Mulia, Kuala Lumpur Malaysia - Wijaya, Anugrah Ricky; Putra, Helwani Fuadi Sujoko; Syah, Alif Alfarisyi; Kusumaningrum, Irma Kartika; Syavika, Lukluatus (Universitas Negeri Malang, 2023)
As a form of concern for the issues faced by the descendants of Indonesian nationals in Malaysia, especially for the Human Resources, we provide the unique theoretical and practical chemistry mentorship for future capability. Sanggar Bimbingan Sungai Mulia 5 is an organization that offers educational services for Indonesian descendants whose citizenship status is still unclear due to administrative reasons. Based on the Chemistry Department UM and Sanggar Bimbingan Mulia cooperation, It is important to enhance the nation's intellectual capacity, especially in ensuring the success of the mandatory 9-year education program. This community service aims to combat illiteracy, in still character education, and prepare students for higher education. The expected outcomes of this program is a unique chemistry Massive Open Online Course (MOOC), a service article published, a service report, and a poster. Our program successfully developed the interest of children to love a simple chemistry experiment and improved for reading and learning through various MOOC, books, and educational materials.